Songlines for Parkinson’s: The Process of Co-Developing a New Music-and-Movement Group-Based Intervention to Improve Mood and Movement for Parkinson’s - Dawn Rose; Marietta Ungerer; Sabrina Köchli; Paolo Paolantonio; Daria Dinacci; Amanda Foletti; Daniele Molteni; Andrew Greenwood; Maria Thomas; Lindsay Truran; Lucy E. Annett; Costas I. Karageorghis; et al. (International Journal of Qualitative Methods)
Participatory research promotes inclusive practice and enables stakeholder expertise to be recognized as a valuable contribution throughout the research cycle. However, there is little guidance regarding how to disseminate these qualitative processes, and the methodological insights gained. Based on preliminary research, we had developed a session framework for a new intervention using music to improve motor and non-motor symptoms for people with Parkinson’s. Our next step was to work in a trans- and interdisciplinary way to further explore concepts (e.g., imagery) and to co-develop content (e.g., musical exercises). Through a synthesis of materials including video footage, worksheets, field notes, transcriptions of interviews and feedback forms derived though workshops and interviews with people with Parkinson’s, a range of practitioners and healthcare professionals, and researchers in the UK (in English) and in Switzerland (in German and Italian), we developed a draft protocol for a 12-week course. This was then optimized through a final round of feedback with the stakeholders. We gained direct methodological insights throughout these processes, including some that led to changes in protocol (addition of two new sections), and the revision (rhythmic exercises) and removal (e.g., singing and syncopation) of some planned content. We also changed our use of language. Indirect insights included the need for cultural and contextual sensitivity, and a new understanding of the bidirectional nature of impact. A new group-based music and movement course, Songlines for Parkinson’s, has been co-developed for and with people with Parkinson’s. The methodological insights gained have not only shaped the protocol but also provided lessons that could be useful for planning and guidance in future participatory projects involving the Parkinson’s community and extended to other groups.